Analisis Isu Kebijakan dalam Pengembangan Kelembagaan Pemerintahan (Studi pada Kelembagaan Penyuluh di Kabupaten Pesawaran) - Mukhlis, Maulana (Jurnal Analisis Sosial Politik, 2020)
In carrying out government functions, local governments are still faced with limited resources, both institutional and personnel. This paper will answer questions about what public policy issues are developing in government institutions (in this case, the extension agency in Pesawaran District) as well as what alternative policy recommendations should be done to address various policy issues in the future. The choice of government institutions in the agricultural sector (including fisheries and forestry) which is supported by two main arguments is not only one of the obligatory functions of the regional government, but also because this sector has proven to be reliable in facing the economic crisis because of the basic livelihoods of the inhabitants of Pesawaran District. Policy research was chosen as the type of research using the interview method and documentation study to obtain primary and secondary data. The results showed that the strategic issues of the institutions in Pesawaran District in general consisted of seven aspects, namely the institutional aspects of extension workers and farmer groups, the quality aspects of the extension workers, the aspects of farmers, the aspects of cooperation, the aspects of infrastructure, the aspects of the implementation of extension, and the aspects of financing. The directives focus mainly on institutional extension workers with the main program for institutional improvement which is compiled on the basis of three references (sources), namely normative sources, regulatory sources, and participatory sources.